MANAJEMEN SUMBER DAYA MANUSIA OUTSOURCING DALAM PERUSAHAAN - Drs Hafulyon (JURIS (Jurnal Ilmiah Syariah), 2018)
Nowadays, Undang-Undang Nomor 13 Tahun 2003 on Labour (Ketenagakerjaan) has become the legal foundation for outsourcing practices in Indonesia. Company management boards who agree to carry out human resources outsourcing are expected to put their priority on market needs, speed, responses and labour flexibility from various perspectives. Consequently, prioritizing efforts to promote company’s efficiency and effectiveness needs to carry out. Among the efforts are sharing some of the works with other parties through outsourcing. Outsourcing management, therefore, should focus on the company’s core business to encourage the company to be more competititive since oursourcing will guarantee the company’s existence for a long term.